Composition and Nature of Humus in Typical Aridisols of Rajasthan - Joshi, D C (Annals of Arid Zone, 2016)
In arid soils bulk of the organic carbon was present in the non humic form. Organic carbon associated with humic and fulvic acid varied from 3.2 to 48.4 and 3.1 to 30 per cent respectively. With increase in silt+c1ay mean values tended to increase slightly for humic and decreases for fulvic acid associated carbon. The humic acids were characterizcd by wcll aromatised, condensed nuclei and their nature was similar in different soils.